The Ethnic Identity and Psychological Well-Being in Migrant Student of Manggarai at the Kupang City - Naben, Jesse Stevany; Damayanti, Yeni; Pello, Shela Christine (Journal of Health and Behavioral Science, 2024)
Migrant students face various challenges during their university studies that can impact their psychological well-being. This research examines the relationship between ethnic identity and psychological well-being among migrant students from the Manggarai tribe in Kupang City. A total of 385 subjects were selected using simple random sampling. The study employed the Multigroup Ethnic Identity Measure (MEIM) scale with a reliability of 0.839, and the Psychological Well-Being scale with a reliability of 0.851. Data analysis was performed using correlation analysis to determine the relationship between the variables. The results reveal a significant positive correlation between ethnic identity and psychological well-being (rxy = 0.076, p = 0.036, < 0.05). This indicates that students with a stronger ethnic identity tend to have better psychological well-being, while those with a weaker ethnic identity report lower levels of well-being. This finding underscores the importance of ethnic identity in supporting the mental health of migrant students.